PELAKSANAAN FUNGSI KELUARGA DALAM MENDIDIK ANAK PADA KELUARGA BROKEN HOME DI RW 04 KELURAHAN TANJUNG HULU - Tika Dwi Azhari; Yohanes Bahari; Maria Ulfah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe title of this research was family function in children education of broken home family at RW 04 Kelurahan Tanjung Hulu. The main problem in this research was what was family function in children education of broken home family. Sub problems in this research were: 1) what was the socialization function in children education of broken home family. 2) what was the affection function in children education of broken home family. 3) what was the education function in children education of broken home family. This research was aimed to describe the family function in children education of broken home family. The method used in this research was qualitative method with descriptive analysis. The tools of collecting data were observation guide, interview guide, and documentation tools. This research showed that: 1) socialization function in children education of broken home family was parents gave understanding and lesson about good and bad things to children. 2) affection function in children education of broken home family was parents gave love and attention to their children. 3) education function in children education of broken home family was parents taught independency, honesty, discipline, and responsibility to children. Keywords: Broken home family, Children education, Family function